Models of Depression: Unpredictable Chronic Mild Stress in Mice. Issue 8 (18th August 2021) - Nollet, Mathieu
Abstract: Major depression is a complex psychiatric disorder characterized by affective, cognitive, and physiological impairments that lead to maladaptive behavior. The high lifetime prevalence of this disabling condition, coupled with limitations of existing medications, make necessary the development of improved therapeutics. This requires animal models that allow investigation of key biological correlates of the disorder. Described in this article is the unpredictable chronic mild stress mouse model that can be used to screen for antidepressant drug candidates. Originally designed for rats, this model has been adapted for mice to capitalize on the advantages of this species as an experimental model, including inter‐strain variability, which permits an exploration of the contribution of genetic background; the ability to create transgenic animals; and lower cost. Thus, because it combines genetic features and socio‐environmental chronic stressful events, the unpredictable chronic mild stress model in mice is a relevant and valuable paradigm to gain insight into the etiological and developmental components of major depression, as well as to identify novel treatments for this condition. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Unpredictable Chronic Mild Stress (UCMS) Test in Mice Basic Protocol 2 : Assessment Of Self‐Directed Activity And Anhedonia in Mice